2018
DOI: 10.21608/omx.2018.5620
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of rhomboid plate in management of subcondylar fractures: prospective randomized controlled trial

Abstract: Purpose: The aim of this study was to compare the clinical and radiological outcomes of treatment of mandibular subcondylar fractures using three-dimensional rhombus plates versus two miniplates techniques. Patients and Methods: A total of 20 patients having subcondylar fractures indicated for open reduction and plate fixation were recruited from Ahmed Maher Teaching Hospital and Faculty of Dentistry, Ain Shams University, and randomly divided into two equal groups. Study group was treated using three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…(11,17,18) Regarding mandibular movements concerning the MMO, ipsilateral, contralateral and protrusive excursions, were satisfactory in all patients of both groups and were regained gradually throughout the follow-up intervals with no statistically significant differences and gives a great support and similarity to that reported in the available literature. (34)(35)(36)(37)(38) In the present study, the Mandibular mobility in-dex and the Helkimo index of mandibular dysfunction showed superior results in the trapezoidal plate group compared to the mini-plates group (P=0.303 and P = 0.528 respectively) and both groups showed a significant improvement by time. Although the difference between groups was statistically insignificant, these results provide superiority for the single trapezoidal plate regarding the rigidity of fixation and postoperative fracture stability.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…(11,17,18) Regarding mandibular movements concerning the MMO, ipsilateral, contralateral and protrusive excursions, were satisfactory in all patients of both groups and were regained gradually throughout the follow-up intervals with no statistically significant differences and gives a great support and similarity to that reported in the available literature. (34)(35)(36)(37)(38) In the present study, the Mandibular mobility in-dex and the Helkimo index of mandibular dysfunction showed superior results in the trapezoidal plate group compared to the mini-plates group (P=0.303 and P = 0.528 respectively) and both groups showed a significant improvement by time. Although the difference between groups was statistically insignificant, these results provide superiority for the single trapezoidal plate regarding the rigidity of fixation and postoperative fracture stability.…”
Section: Discussionsupporting
confidence: 48%
“…The results of our study give a great support to those of a recent study done in 2018, by Mahmoud F.et al, (37) who evaluated the efficiency of application of the 3D Rhombic plates in the fixation of displaced low subcondylar fractures and concluded that the 3D Rhombic plates were compatible for treatment of condylar fractures and provided satisfactory stable fixation. (38) in 2018 in their prospective randomized controlled clinical trial compared the outcomes of the 3D rhombic plates with the 2.0 miniplates in management of subcondylar fractures.…”
Section: Meyer Et Al In 2007mentioning
confidence: 99%
“…[5][6] That provides the advantage of easier placement especially in the small proximal segments. [17] Moreover, it offers reduction of the total treatment fees, as it has cheaper hardware and shorter operative time as less plate and screws are required. [18][7] A rhombic 3D plate was introduced as a modification to the delta plate, changing the three sided delta shape into a four sided rhombic design and adding an extra screw to improve stability and biomechanical properties of the plate.…”
Section: Introductionmentioning
confidence: 99%